Combination of rituximab and nonpegylated liposomal doxorubicin (R‐NPLD) as front‐line therapy for aggressive non‐Hodgkin lymphoma (NHL) in patients 80 years of age or older: a single‐center retrospective study. Issue 1 (3rd February 2017) - Ricciuti, Giuseppina; Finolezzi, Erica; Luciani, Stefania; Ranucci, Elena; Federico, Massimo; Di Nicola, Marta; Zecca, Isaia Antonio Luca; Angrilli, Francesco
Abstract: The incidence of non‐Hodgkin lymphoma in patients 80 years of age or older is 50 times higher than in 20‐ to 24‐year‐olds. Very elderly patients are often not treated with standard immunochemotherapy because of poor performance status, comorbidities, and toxicity concerns. We retrospectively analyzed data for 29 patients diagnosed with diffuse large B‐cell lymphoma or grade 3B follicular lymphoma and treated with rituximab in combination with nonpegylated liposomal doxorubicin between January 2010 and August 2015. The median age was 84 years. The overall 3‐year survival, cause‐specific survival, and progression‐free survival rates were 46%, 55%, and 44%, respectively. Among prognostic factors, only the achievement of complete remission strongly correlated with overall survival, cause‐specific survival, and progression‐free survival rates. Treatment caused very mild toxicity, without treatment‐related hospitalization or toxic deaths.